Travel fatigue and jet-lag - Reilly, T.; Atkinson, G.; Waterhouse, J. (Journal of Sports Sciences, 1997)
Travel across multiple time zones is a common feature of the lifestyle of contemporary international sport competitors. This entails a disruption of the body's circadian timing mechanisms. Symptoms of 'jet-lag' persist until circadian rhythms re-tune into local time. Exercise performance may be impaired during the period of adjustment to the new time zone. Behavioural and pharmacological strategies are available to help accelerate the resynchronization of circadian rhythms. It is recommended that sports administrators should consider the consequences of jet-lag and the time needed to overcome it when planning the international itineraries of travelling athletes.